PERCEPTION OF CUSTOMERS ON THE ELEMENTS OF CSR WITH SPECIAL REFERENCE TO PUBLIC SECTOR BANKS IN TIRUNELVELI (International Journal of Food and Nutritional Sciences, 2022)
Corporate Social Responsibility (CSR) is a concept that suggests that it is the responsibility of the corporations operating within society to contribute towards economic, social and environmental development that creates a positive impact on society at large. The level of its impact on customers shall be measured by using some techniques. In the present study the researcher has concentrated on the view and perception of customers and their attitude towards the achievement of CSR of banking sector particularly in the study area and analysed by using statistical tools like percentage analysis, factor analysis, Garrett ranking technique etc.